PENGEMBANGAN MATERI KONSEP DIRI SISWA KELAS XI IPS2 SMA NEGERI 2 TAMBANG KABUPATEN KAMPAR TAHUN AJARAN 2013/2014 - Muhammad Riduwan; Sardi Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abtract: The lack of a positive self concept of students and limited material about self concept, encourage the researcher to conduct a development research that a compilation self concept of material class XI IPS2 SMA NEGERI 2 Tambang students. The aimed of research: 1). Compose material concept of self that is suitable for students of class XI IPS2 SMAN 2 Tambang in terms of clarity, aspects, systematics, image support, update, and completeness of the materials. 2) To Know the quality of materials self concept that produced. using of research and development method. as validators are guidance lecturer I, guidance lecturer II, one of BK FKIP UR lecturer, tutor teacher, 6 friends of the associate PL-BKS, and 30 students of class XI IPS2 SMA NEGERI 2 Tambang. The material self concept consists of 4 sub chapter : 1).the meaning of self concept. 2). components of self concept. 3). Factors influenced self concept. 4). Existenceof self concept. Quality of self concept materials that produced based of clarity aspect is very good with X = 3,60. Systematic aspect is very good with X = 3,52. Image support aspect is very good with X = 3,42. Update of material aspect is very good with X =3,67. Compliteness of materials aspect is good with X = 3,35. And from all of aspect is concluded very good quality, with X = 3,51.Key word: Material of self concept